Evaluation of Quality Protein Maize Inbred Lines for Turcicum Leaf Blight and Gray Leaf Spot at Bako, Ethiopia - Debela Diro; Temesgen Hunde; Mideksa Ardessa (Al-Qadisiyah Journal For Agriculture Sciences, 2023)
Currently, Ethiopia has the second-highest national average yield reported in Sub-Saharan Africa (SSA), only below South Africa. But maize production in Ethiopia is constantly threatened by the potential outbreak of major foliar diseases such as turcicum leaf blight (TLB) and gray leaf spot (GLS). These diseases are characterized by relatively rapid leaf necrosis and premature death of foliage which eventually reduces grain yield. The diseases become a major problem in all major maize growing areas. Development of host resistance to these diseases can provide an important component of integrated disease management; which is the most effective and practical method of managing maize diseases. The study was conducted to evaluate the reaction of quality Protein maize inbred lines to TLB and GLS in the main cropping season during 2018. The inbred lines were obtained from Bako National Maize Research Center, breeding program, and it was arranged using alpha-lattice design with two replications and the inbred lines were inoculated with TLB and GLS disease inoculum under field condition and the experiments were set in separate field trial in respective disease. Disease severity (1-5 scale) was used to assess at ten days intervals from disease onset until the maize attained senescence. All the inbred lines showed symptoms of both diseases during the season, but the intensity of the diseases differed significantly (P<0.05) among the inbred lines. Accordingly, out of 42 genotypes screened for both TLB and GLS, lines MBRC5BcF108-2-3-1-B-5-2-B-B-#,Obatanpa-5-4-1-1-1-#-#-#,([[[CML159/[CML159/[MSRXPOOL9]C1F2-205-1,(OSU23i)-5-3-X-X-1-BB]F2-3sx]-8-1-B-B/CML509]F2 1/[GQL5/[GQL5/[MSRXPOOL9]C1F2-205-1(OSU23i)-5-3-X-X-1-BB]F2-4sx]-1-1-3-1-1B*4]-12/CML373IR)-B-8-B-7-2-1-B-#-#-#,(CML176xKULENI(F2)-4-3-1-1-1-#-#,(CUBA/GUADC1F27-4-3-3-B-1-BX[KIiIMAiTA94A]-30MSV-03-2-10-B-2-B-B)-306-1-B-2-B-B-B-#, based on a 1–5 rating scale system for disease severity, they were selected as resistant.